Evaluation of energy band structure of half-heusler alloy LiZnX (X = As, P and Sb) using first principle calculation - Ettah, Emmanuel; Ishaje, Michael E.; Minakova, Kseniia; Asuquo, Esther Offiong; Odey, Stephen U. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The evaluation of energy band structure plays a vital role in understanding the electronic properties of materials. This research, we investigate the energy band structure of Half-Heusler alloys LiZn(X = As, P and Sb) using a first principle approach based on Density Functional Theory (DFT). These alloys are of particular interest due to their potential applications in thermoelectric and spintronics devices. The corresponding Density of States (DOS) for the tripartite compounds LiZnX (X=As, P and Sb) have been calculated and the contributions of the Li, Zn, As, P and Sb orbital to the Density of States at ambient pressure. This also confirmed that LiZnX (X=As, P and Sb) is a semi-conductor with a narrow band-gap between the occupied and unoccupied regions around the Fermi level. The orbitals Li-1s, As-4p, As-4s, Zn-3d has the highest contributions. The dominant of the orbitals P-1s and P-2p before the Fermi- level and Zn-2p after the Fermi-level are observed. We observed the dominant of the orbitals Sb-1s, Sb-3d, Li-1s, Li-2s, Zn-3d shows weak hybridization and low contribution. This features indicates that the covalent bond between these two atoms is weak, and could be responsible for the mechanical instability observed in the calculation. Meanwhile the band structure calculated and presented has narrow band-gab of 0.625. 0.937 and 0.313 respectively for the tripartite compound LiZnX(X=As, P, and Sb) and its a direct bandgap semiconductor. The obtained energy band structures provide valuable information about the electronic properties of LiZn (X = As, P and Sb) alloys. The presence of band gaps is crucial for thermoelectric applications, as it indicates the presence of regions where electrons and holes are confined, enabling efficient charge transport.

Оцінка структури енергетичних зон відіграє важливу роль у розумінні електронних властивостей матеріалів. У цій роботі представлено дослідження структури енергетичних зон напівгерселерових сплавів LiZn (X = As, P та Sb) за допомогою підходу першого принципу, основаного на теорії функціонала густини (DFT). Ці сплави є особливо цікавими через їх потенційні застосування в термоелектричних та спінтронічних пристроях. Відповідна густина станів (DOS) для тричасткових сполук LiZnX (X = As, P та Sb) була розрахована, і внески орбіталей Li, Zn, As, P та Sb до густини станів при атмосферному тиску були визначені. Це також підтвердило, що LiZnX (X = As, P та Sb) є напівпровідником із вузькою забороненою зоною між зайнятими та незайнятими областями навколо рівня Фермі. Орбіталі Li -1s, As-4p, As-4s та Zn-3d мають найбільший внесок. Спостерігається переважання орбіталей P-1s та P-2p перед рівнем Фермі та Zn-2p після рівня Фермі. Також спостерігається переважання орбіталей Sb-1s, Sb-3d, Li-1s, Li-2s, Zn-3d зі слабкою гібридизацією та низьким внеском. Це свідчить про слабкий ковалентний зв'язок між цими двома атомами, що може бути відповідальним за спостережену механічну нестійкість при розрахунках. Тим часом розрахована та представлена структура енергетичних зон має вузьку заборонену зону розміром відповідно 0.625, 0.937 та 0.313 для тричасткової сполуки LiZnX (X = As, P та Sb), і це прямий напівпровідник з забороненою зоною. Отримані структури енергетичних зон надають цінну інформацію про електронні властивості сплавів LiZn (X = As, P та Sb). Наявність забороненої зони є важливою для термоелектричних застосувань, оскільки це вказує на наявність областей, де електрони та дірки обмежені, що сприяє ефективному транспорту заряду.
Оцінка енергетичної зонної структури напівгерслерового сплаву LiZnX (X = As, P та Sb) за допомогою першого принципного розрахунку
Keywords: energy band structure; Half-Heusler alloys; density functional theory; DOS; semiconductor; band-gap; структура енергетичних зон; напівгерслерові сплави; теорія функціонала густини; густина станів; напівпровідник; заборонена зона